Perancangan dan Pendampingan Pembangunan Masjid Nurul Huda, Kuala Teladas, Kec. Dente Teladas, Kab. Tulang Bawang, Lampung - Kurniawan, Panji; Nugroho; B, Kelik Hendro; Ifadianto, Nugroho; Agumsari, Dini; Rusmiati, Fadhilah; C, Agung; Adi, Nur (Nemui Nyimah, 2024)
The service activities carried out include technical assistance in the form of design drawings and outreach to local religious and community leaders in providing an overview of the development plans and processes of the Nurul Huda Development Plan which is located in the Kuala Teladas area, Kec. Dente Teladas, Kab. Onion bones, Lampung. This Community Service activity is part of the implementation of the Tri Darma of Higher Education which is one of the obligations as an academic. The aim of this service is to help the community in the increasingly worrying process of building the Nurul Huda Mosque, Kuala Teladas. Especially for technical document drawings, to be able to estimate space requirements, room layout, location of mosque supporting facilities in a technical drawing. This is important because the existing condition of the land is located at the mouth of the Tulang Bawang river and the water level is higher than the mosque building. This design drawing will also make it easier for the committee, the community and development implementers to align their perceptions about the development plan starting from the layout, space requirements to the shape of the mosque after it is built. The plan for preparing this design document will go through several discussions, measurements and presentations to relevant stakeholders, which in this case are the congregation, community, religious leaders, potential donors as well as the development committee, so that the development design ideas that will be created by the team can be in accordance with hope of all parties. It is hoped that this design drawing will also be able to help the committee not only in the development implementation process, but also in disseminating information, so that it can become material for making proposals to raise funds from development donors.